2017
DOI: 10.1038/s41598-017-05293-1
|View full text |Cite
|
Sign up to set email alerts
|

The temperature sensitivity of soil organic carbon decomposition is greater in subsoil than in topsoil during laboratory incubation

Abstract: The turnover of soil organic carbon (SOC) in cropland plays an important role in terrestrial carbon cycling, but little is known about the temperature sensitivity (Q 10 ) of SOC decomposition below the topsoil layer of arable soil. Here, samples of topsoil (0-20 cm) and subsoil (20-40 cm) layers were obtained from paddy fields and upland croplands in two regions of China. Using a sequential temperature changing method, soil respiration rates were calculated at different temperatures (8 °C to 28 °C) and fitted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 56 publications
2
39
0
Order By: Relevance
“…respiration increased rapidly at the early stage of incubation (0-15 DAI), decreased rapidly during mid incubation (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and then decreased relatively slightly during the later stage of incubation (31)(32)(33)(34)(35)(36)(37)(38)(39)(40). These changes in SR suggested that labile organic matter may have depleted quickly along with incubation time as observed in previous studies [6].…”
Section: Plos Onesupporting
confidence: 58%
See 1 more Smart Citation
“…respiration increased rapidly at the early stage of incubation (0-15 DAI), decreased rapidly during mid incubation (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and then decreased relatively slightly during the later stage of incubation (31)(32)(33)(34)(35)(36)(37)(38)(39)(40). These changes in SR suggested that labile organic matter may have depleted quickly along with incubation time as observed in previous studies [6].…”
Section: Plos Onesupporting
confidence: 58%
“…Increasing temperature would stimulate soil microbial metabolisms [15], accelerate SOC decomposition [16] and increase C efflux through SR [17]. Since the temperature sensitivity of SR (Q 10 ) varied with the substrate availability [18], how the comprehensive responses of C soil fractions, SR and microbial communities to straw mulching would vary with different temperature change is now well reported. Here, we carried out an incubation study, aimed to (1) determine changes in carbon fractions and SR rates to different temperatures in soils with and without 9-yr straw mulching, (2) quantify the effect of straw mulching on soil temperature sensitivity; and (3) explore the relationships among soil C fractions, SR rates and the soil microbial community.…”
Section: Introductionmentioning
confidence: 99%
“…Our results showed that soil microbial respiration in the deep soil had significantly greater temperature sensitivity (1.91–2.11) than in the topsoil (Figure ). These results support the “C quality‐dependent hypothesis” that recalcitrant compounds with more activation energy have larger Q 10 (Bosatta & Agren, ), and they are also consistent with other observations from several long‐term laboratory incubation studies (Xu, Li, Jiang, Wang, & Bai, ; Yan et al, ). Soil microbial communities are generally C‐limited, suggesting that substrate availability can be important in mediating warming effects on microbial respiration (Gershenson, Bader, & Cheng, ).…”
Section: Discussionsupporting
confidence: 90%
“…However, experimental results are variable. Some studies showed that C mineralization was more sensitive to temperature increases in deep soil rather than topsoils (Yan et al, ), whereas others reported either a similar response (Pries et al, ) or even slower responses (Pang, Zhu, Lu, & Cheng, ). Similarly, the response of recalcitrant soil C decomposition to newly added C substrates (i.e., the priming effect) in deep soils has been shown to be either larger (Fontaine et al, ; Tian et al, ) or smaller than in topsoils (Kuzyakov, ).…”
Section: Introductionmentioning
confidence: 99%
“…CO 2 flux measured at a single location in situ may not be representative due to soil heterogeneity at the field scale. Excavation of soil, followed by ex situ measurement of soil respiration under controlled conditions, is often performed to compare soils or test specific hypotheses (Gutinas et al 2013;Zhou et al 2014;Bao et al 2016;Yan et al 2017), while minimizing confounding factors. Whereas in situ measurements are more representative of the actual field conditions (Gabriel and Kellman 2011), ex situ measurements can be used to apply treatments in a systematic manner and are thus very useful.…”
Section: Introductionmentioning
confidence: 99%